Greater estimated fetal weight and birth weight in IVF/ICSI pregnancy after frozen–thawed vs fresh blastocyst transfer: prospective cohort study with novel unified modeling methodology. (1st July 2022) - Cavoretto, P. I.; Farina, A.; Gaeta, G.; Seidenari, A.; Pozzoni, M.; Spinillo, S.; Morano, D.; Alteri, A.; Viganò, P.; Candiani, M.
Abstract: Objective: To compare, using a unified approach, standardized estimated fetal weight (EFW) trajectories from the second trimester to birth and birth‐weight (BW) measurements in in‐vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) pregnancies obtained after frozen–thawed vs fresh blastocyst transfer (BT). Methods: This was a secondary analysis of a prospective longitudinal cohort study performed at the Fetal Medicine and Obstetric Departments of San Raffaele Hospital in Milan, Italy, from January 2016 to December 2020. Eligible for inclusion were singleton viable gestations conceived by autologous IVF/ICSI conception after fresh or frozen–thawed BT that underwent standard fetal biometry assessment at 19–41 weeks and had BW measurements available. All ultrasound assessments were performed by operators blinded to the employment of cryopreservation. Patients with twin gestation, significant pregestational disease, miscarriage, major fetal abnormalities and use of other types of medically assisted reproduction techniques were excluded. EFW and BW Z ‐scores and their trajectories were analyzed using general linear models (GLM) and logistic regression with a unified modeling methodology based on the Fetal Medicine Foundation fetal and neonatal population weight charts, adjusting for major confounders. Differences between prenatal EFW and postnatal BW centiles in the two groups were assessed and compared using contingency tables, χ 2 test and conversion of prenatal to postnatal centiles. Results: A total of 631 IVF/ICSI pregnancies were considered, comprising 263 conceived following fresh BT and 368 after frozen–thawed BT. A total of 1795 EFW observations were available ( n  = 715 in fresh BT group and n  = 1080 in frozen–thawed BT group; median of three observations per patient). EFW and BW < 10 th centile were significantly more frequent in the fresh than in the frozen–thawed BT group ( P  = 0.003 and P  < 0.001, respectively). EFW and BW > 90 th centile were significantly more frequent in the frozen–thawed vs fresh BT group ( P  = 0.034 and P  = 0.002, respectively). GLM showed significantly decreasing EFW Z ‐scores with advancing gestational age (GA) in both groups. The effect of GA was assumed to be equal in the two study groups, as no significant interaction effect was found. Smoothed mean EFW Z ‐scores from 19 weeks of gestation to term and smoothed mean BW Z ‐scores were both significantly higher in the frozen–thawed compared with the fresh BT group (EFW Z ‐score, 0.70 ± 1.29 vs 0.28 ± 1.43; P  < 0.001; BW Z ‐score, 0.04 ± 1.08 vs −0.31 ± 1.28; P  < 0.001). Mean smoothed EFW Z ‐score values in the frozen–thawed vs fresh BT groups were 1.01 ± 0.12 vs 0.60 ± 0.08 at 19–27 weeks, 0.36 ± 0.07 vs −0.06 ± 0.04 at 28–35 weeks and −0.66 ± 0.01 vs −0.88 ± 0.02 at 36–41 weeks. Mean smoothed BW Z ‐score values in the frozen–thawed vs fresh BT groups were −0.80 ± 0.14 vs −1.20 ± 0.10 at 28–35 weeks and 0.22 ± 0.16 vs −0.24 ± 0.14 at 36–41 weeks. Assessment of EFW and BW concordance showed a significantly greater rate of postnatal confirmation of prenatally predicted small‐for‐gestational age (SGA) < 10 th centile in the fresh compared with the frozen–thawed BT group ( P  < 0.001), whereas the rate of postnatal confirmation of large‐for‐gestational age (LGA) > 90 th centile was significantly higher in the frozen–thawed vs the fresh BT group ( P  < 0.001). Logistic regression analysis showed that the smoothed rate of EFW < 3 rd centile was about 6‐fold higher in the fresh vs frozen–thawed BT group ( P  < 0.001), whereas the smoothed rates of EFW 90 th –97 th centile and > 97 th centile were nearly double in the frozen–thawed compared with the fresh BT group ( P  < 0.05 and P  < 0.001, respectively). Conclusions: Robust novel unified prenatal–postnatal modeling in IVF/ICSI pregnancies after frozen–thawed or fresh BT from 19 weeks of gestation to birth showed non‐divergent growth trajectories, with higher EFW and BW Z ‐scores in the frozen–thawed vs fresh BT group. The mean EFW Z ‐scores in both IVF/ICSI groups were greater than those expected for natural conceptions, being highest in the midtrimester and decreasing with advancing gestation in both groups, becoming negative after 32 weeks in the fresh and after 35 weeks in the frozen–thawed BT group. Mean BW Z ‐scores were negative in both groups, with lower values in preterm fetuses, and increased with advancing gestation, becoming positive at term in the frozen–thawed BT group. IVF/ICSI conceptions from frozen–thawed as compared to fresh BT presented increased rate of LGA and reduced rate of SGA both prenatally and postnatally. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.